Optimal timing of product launch with minimal effect of cannibalization - Heng, Owyong. (2010)
A close examination of previous studies has shown that over the years, many researchers have realized the fact that the timing at which a firm launches a new or upgraded product is a vital but intricate decision for the firm. Hence, for this reason, many researchers have analyzed and come out with models to help the firms to determine their optimal timing of product launch. However, among all these models, there is one thing in common, and that is they do not take the effect of cannibalization into consideration. Thus this project will take the analysis a step further and aims to help the firms to locate their optimal timing of product launch with minimal effect of cannibalization. This is in condition that the firms are technologically ready to launch the new or upgraded product.